Hubungan Fasilitas dan Kepuasan Mahasiswa di Klinik Perawatan Mulut di Departemen Perawatan Gigi - Yuniarly, Etty; Ismaniati, Christina; Haryani, Wiworo (Journal of Oral Health Care, 2018)
Laboratory or clinic is a facility for students to practice the skills required in practical situation. The completeness of existing facilities and infrastructure in the laboratory or clinic can supportquality improvement in practice the concept that has been overrun by students to enhance their learning achievements. Learners will be able to maximize the use of laboratory if facilities are complete and meet the learning needs. That was research used analytic observational approach cross sectional (cut the latitude) designed by doing observations at the same time. This research was carried out in the oral nursing care clinic in Dental Nursing Department. Total samples were 73 students semester IV, wich was taken with the total sampling method. Data collection used questionnaire. Data analysis techniques used correlation analysis Kendall Tau test. The results of analysis with Kendall Tau test by used a confidence level of 95% (? = 0.05) obtained results ?-value = 0.00 and coefficient correlations (means) and 0.54 0.52 (infrastructure), the better or complete facilities and infrastructure, the more satisfied students in practise in clinic Conclusion: There was a relationship facilities (infrastructure) and satisfaction of students at oral nursing nursing care clinic in Dental Nursing Department